Observations on a parasitic nematode (Tetradonematidae) of fire ants, Solenopsis (Formicidae), from Mato Grosso - Jouvenaz, Donald P.; Wojcik, Daniel P.; Naves, Marcio A.; Lofgren, Clifford S. (Pesquisa Agropecuaria Brasileira, 2014)
Parasitic nematodes, Tetradonema sp. (Mermithoidea: Tetradonematidae) were observed in the fire ant, Solenopsis invicta Buren, for the first time. Five colonies in a sample of 14 colonies from one site in Mato Grosso were infected. The infection rate among adult workers was 12.5% in one colony and less than 5% in each of the remaining colonies. Adult reproductive males and females, eggs, and juvenile nematodes were observed in the haemocoel of male and worker ants. The infected worker ants often can be recognized by their slightly enlarged gasters, the dorsal sclerites of which may have a scalloped appearance. There are no other morphological signs of infection and no observable changes in behavior. lnfected adult males contained normal sperm. An attempt to transmit the nematode to colonies of S. invicta in the United States was unsuccessful.